618.MANAGING ORGANIZATIONAL CHANGE IN COMMUNAL PUBLIC ENTERPRISES:A LITERATURE REVIEW - Georgi, Hristov; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
This work presents a literature review regarding the organizational change. The resistance to change – a “natural associate” on change – was not considered as a separate topic under the scope of this work. More than thirty academic articles were reviewed and analyzed. An effort was done to link, to confront and, whenever possible, to compare the different findings about the organizational change as found by the academic research. In general, the review focuses on the organizational change literature and, in particular, the available peer reviewed academic articles that focus on the organizational change in public sector. The influence of different factors and behaviours (employees’ participation and commitment, the change context, the management and leadership support, timing, communication and strategic change process) over the change process was examined. Some models for implementation the change process and the revolutionary change are mentioned. The concept of changing “whole system” is also mentioned as an important one when speaking about the change in public sector. The lack of research regarding the organizational change in communal public enterprises is noted and suggestions for further research are given.